25‐2: Invited Paper: Ultra‐High‐Resolution NanoLED Panel for AR/VR by UV Patterning Technology. Issue 1 (28th June 2022) - Tsujino, Kazuya; Kosaka, Tomohiro; Daio, Manabu; Ootsuka, Yuuki; Orita, Kunihiko; Teranishi, Tomoko; Ishida, Takeshi; Minoura, Kiyoshi
Abstract : We report and discuss UV patterning technology of nanoLED with ultra‐high‐resolution. Additionally, we also report on the performances of the ultra‐high‐resolution nanoLED panel for ARJVR by UV patterning technology.